Development of Interactive Learning Media Based on Articulate Storyline to Improve Student’ Science Literacy - Ramadhani, Indri Anugrah; Asrul, Asrul (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
The students’ low scientific literacy may come from some factors, one of them is that the students does not play a direct active role in the learning process, which the result shows that the students only learning by rote without understanding the concepts of the material being studied, so there are many students does not understand the concepts of science. The aim of this research is to develop interactive learning media according to Articulate Storyline to increase scientific literacy for elementary school students. The type of research used is research and development (R&D) with the ADDIE development model. The field test involved 20 students as participants. Data collection techniques were carried out using observation, interview, documentation, questionnaire, and test techniques. The needs analysis is carried out through interviews with students and classroom teachers. The second stage involves Design. The third stage is Development. The fourth stage involves product implementation. The final stage involves conducting an evaluation. The results of this research were interactive learning media based on Articulate Storyline, which showed that the validity test results got an average score of 86% in the very valid category and the effectiveness test results got a score of 0.69 in the medium category, so it can be conclude that the interactive learning media according to Articulate Storyline on Earth, Sun, and Moon material are valid and effective in increasing the scientific literacy of elementary school students.